Establishment Of Religious Character For “Suku Anak Dalam” (Study Of Sad Students At Madrasah Fathul Huda Singkut Jambi) - Ikhwan Hidayana; Muslih Hidayat; Zuhri Zuhri (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2023)
Suku Anak Dalam (SAD) is one of the original Jambi tribes who exited themselves to theinterior of the forest. That’s why they are also called jungle people. Their bigotry with theoutside world is one of the reasons they do not want to receive an education. Some ofthose who are willing to accept modernization today are sending their children to formalschools such as the one at MIS Fathul Huda Pasar Singkut Village.This research is descriptive qualitative. The data were collacted through observation,interviews and documentation.This research found that: the condition of the religious character SAD students in MISFathul Huda is currently progressing than before; the strategy used in shaping thereligious character of SAD students in MIS Fathul Huda is a habituation strategy; and thefactors that support the implementation of this strategy are teachers, living environtment,and parent’s motivation, while the inhibiting factors are the students themselves, andtheir home environment